Association Between Metabolic Syndrome and an Increased Risk of Hospitalization for Heart Failure in Population of HFpEF - Zhou, Ying; Fu, Liyao; Sun, Jiaxing; Zhu, Zhaowei; Xing, Zhenhua; Zhou, Shenghua; Tai, Shi; Wang, Yongjun (Frontiers in Cardiovascular Medicine, 2021)
Background: Association between metabolic syndrome and development of the heart failure (HF) with preserved ejection fraction (HFpEF) are not completely clarified. Aim: To evaluate the association between metabolic syndrome and the risk of HF hospitalization in patients with HFpEF. Methods: Data were obtained from the American cohort of the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT) trial database. The primary outcome (hospitalization for HF) and secondary outcomes (included all-cause mortality, cardiovascular mortality, all-cause hospitalization) was collected. Hazard ratios (HRs) in patients with metabolic syndrome and without metabolic syndrome were analyzed and performed by multivariable Cox proportional hazard model. Results: Among 1,548 participants, 1,197 had metabolic syndrome. Patients with metabolic syndrome had worse heart function and lower quality of life than those without it. During 3.3 years follow-up, 351 patients were hospitalized for HF. After multivariable adjustment, the risk of hospitalization for HF and all-cause hospitalization (adjusted HR = 1.42, 95% CI: 1.01-2.00; p = 0.042 and adjusted HR = 1.27; 95% CI: 1.04-1.54; p = 0.017, respectively) was independently associated with HFpEF patients with metabolic syndrome. Among propensity score-matched patients (n=267), the risk of HF hospitalization and all-cause hospitalization were also higher in patients with metabolic syndrome (HR= 1.53, 95% CI= 1.05-2.23, and p = 0.025 and HR= 1.34, 95% CI= 1.08-1.67, and p = 0.009, respectively). Conclusions: The risks of HF hospitalization and all-cause hospitalization were higher in HFpEF patients with metabolic syndrome than in those without metabolic syndrome.